2020
DOI: 10.21203/rs.3.rs-64077/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical decision support improves the appropriateness of laboratory test ordering in primary care without increasing diagnostic error: the ELMO cluster randomized trial

Abstract: BackgroundInappropriate laboratory test ordering poses an important burden for healthcare. Clinical decision support systems (CDSS) have been cited as promising tools to improve laboratory test ordering behavior. The objectives of this study were to evaluate the effects of an intervention that integrated a clinical decision support service into a computerized physician order entry (CPOE) on the appropriateness and volume of laboratory test ordering, and on diagnostic error in primary care.MethodsThis study was… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…This CDS is integrated into a computerized physician order entry (CPOE) to examine the appropriateness and volume of laboratory test ordering and diagnostic errors in primary care. The results show that a CDS within the CPOE improves the appropriateness of lab tests and decreases the volume of laboratory test ordering without increasing diagnostic error [28].…”
Section: Industrialized Countriesmentioning
confidence: 94%
“…This CDS is integrated into a computerized physician order entry (CPOE) to examine the appropriateness and volume of laboratory test ordering and diagnostic errors in primary care. The results show that a CDS within the CPOE improves the appropriateness of lab tests and decreases the volume of laboratory test ordering without increasing diagnostic error [28].…”
Section: Industrialized Countriesmentioning
confidence: 94%
“…For example, in a seminal work published by one of us nearly 10 years ago, we showed that the adoption of a computerized alert system based on specific re-testing intervals and encompassing the appearance of flexible alerts (i.e., ignorable pop-ups) when a set of predefined appropriateness criteria were violated by the prescribing physicians, was effective to generate a nearly 80% reduction in the burden of theoretically inappropriate tests, accompanied by an approximately 13% decrease of total laboratory costs [13] . In another experience, Delvaux et al [14] developed a clinical decision support systems (CDSS) encompassing a series of evidence-based order sets aimed at proposing the more appropriate lab tests according to the clinical indications provided by the prescribing physician. The authors showed that such system not only was effective to significantly enhance the number of appropriately requested tests by over 50%, but was also associated with significant decrease in potential diagnostic errors.…”
Section: Introductionmentioning
confidence: 99%